The emotional politics of research collaboration - Griffin, Gabriele; Branstrom Ohman, Annelie; Kalman, Hildur (New York : Routledge, 2013)
'Research collaboration in the form of networks, projects and centers has become one of the dominant modes of engaging in research, especially funded research, across all academic domains. However, there has been little research on the processes of such collaborations, particularly their affective dimensions. These, as this volume demonstrates and as researchers know well, are highly important, yet mostly not directly engaged with when scientists work together, even though they are experienced by everybody involved. This volume is the first to consider questions such as how the naming of projects impacts on their accompanying'affect-scapes,' the policing or disciplining of emotions in research collaborations, their accompanying tensions and how these might be managed, and the challenges to trust between scientists that such collaborations present. Drawing on theories of affect and literature on collaboration, as well as on the contributors' experiences of being involved in large-scale research projects, the volume also importantly deals directly with some of the key emotions that occur during research collaborations such as blame, elation, frustration, alienation and belonging, and suggests some ways in which one might engage productively with the affective dimensions of research collaboration'--
Includes bibliographical references and index.
Keywords: Research -- Psychological aspects; Feminism and science